Is energy drink safe? A cross sectional study on the effects of energy drink on medical students from a medical school of Nepal - Banerjee, Indrajit; Pugazhandhi, B; Banerjee, I; Sathian, B; Nagpal, P; Roy, B (Nepal Journal of Epidemiology, 2015)
Background: Energy drinks that contain caffeine, taurine, vitamins, herbal supplements, sugar or sweeteners are marketed to improve energy, weight loss, stamina, athletic performance and concentration. Recently some of energy drink has been banned in different countries like Saudi Arabia. In Nepal none of the studies has been done to report the effect of energy drink on health. The main objective of the study was to find out the effect of energy drink on health of medical students. Materials and Methods: It was a cross sectional questionnaire based study done at Manipal College of Medical Sciences, Pokhara, Nepal on November 2013. Results: Out of 206 students 202 completed the questionnaire completely and their responses were evaluated which gives an overall response rate of 98.05%%. Out of 202 students, 88 (43.56%) students were found consuming energy drinks. The research finding revealed that most of the students who consumed energy drink were male 58%. Most of the students felt energetic after consuming energy drink. The majority of the students were from the second year 79.5%. The majority of the students, 71.6% consumed < 5 cans/week. Among the CNS manifestations students felt energetic, insomnia, euphoria, anxiety, dizziness, hallucination, headache and seizure disorder. Most of the students suffered from palpitation among the CVS manifestations. Other GIT and CVS Manifestations were discomfort, nausea, vomiting, diarrhoea, abdominal pain, constipation, weight loss and chest pain. ANS and miscellaneous manifestations were also seen among the students among which increased stamina , micturation, dry mouth, sweating, burning sensation in the throat, allergic reactions, breathlessness were noted by the students. Headache and insomnia was found more prevalent in males [OR 1.836 95% (CI 0.458, 7.367)] and [OR 1.214, 95 %(CI 0.517, 2.852)], respectively as compared to female students. However, in the case of GIT manifestations viz. abdominal pain and constipation revealed that it was more prevalent among male students [OR 2.292, 95 %(CI( 0.343, 13.638)] and [OR 1.836, 95 %(CI 0.458, 7.367)]. Conclusion: It is concluded that energy drink gives energy and increases the stamina but it produces neurologic, psychiatric, cardiovascular and gastrointestinal complications on health. Further studies are required on the same field to find out its effect on health in Nepalese population.